WTO dispute settlement cases involving Latin American countries and the agreement on agriculture, 1995-2019 - Gonzalez, Anàbel; Glauber, Joseph W. (Instituto Interamericano de Cooperación para la Agricultura, 2021)
Latin America, as a lead exporter of agricultural products, has a significant interest in open global markets. The region’s agriculture trade surplus has increased to U$54 billion in 2016-2018 from US$12 billion in 1996-1998. Brazil and Argentina, the first and second top agricultural and food exporters in the region, rank third and tenth worldwide and lead world exports of soybeans, maize, vegetables oils, sugar, poultry and beef. Mexico, Chile, Ecuador, Peru and some Central American countries have also seen significant dynamism in their exports of fruits and vegetables (OECD-FAO, 2019).